Typology of children’s television audience: to the problem of children’s perception of the content of programs (Herald of Journalism, 2022)
In this paper, an attempt is made to consider the typology of a children’s television audience. Ty- pologization of the children’s audience will help to identify the characteristics of each group of viewers, its needs and interests, to determine everything that is necessary to optimize children’s broadcasting. The typology method adopted in this study is widely used in the natural sciences. Currently, he finds applica- tion in the humanities, in particular, in journalism. The author also considers the specifics of the national children’s audience. In the process of previous life experience, the language that children have learned imposes on them as their ways of seeing the world. There is no guarantee that we do not perceive, we do not model the world through the peculiar prism of our native language. This allows us to address the problem of children’s perception of the content of television programs. As is known, the transmission reflects a predominantly visual situation, and not its verbal description. Therefore, the telecast is the most appropriate for the nature of children, as they think in similar ways. You can transfer these images by translating your own code into a verbal (acoustic) one. The TV frame has an advantage over other media: the telecast causes visual images of young spectators. They are transmitted on the same code as children think. In spite of the fact that researches have recently appeared that consider the problem of forming the visual image, the process of translating information in the form of acoustic or visual code into the child’s internal code remains unclear.Key words: typology, psychology, the nature of children, the content of telecasts, verbal code, visuallanguage.